Pengembangan E-modul Berbantuan Software Algebrator pada Materi Bilangan Berpangkat dan Bentuk Akar Kelas X SMK - Mei Yuriska Putri; Leo Adhar Effendi; Sri Rezeki; Endang Istikomah (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
The use of technology in education has a significant impact in educating and educating the nation's life, and can help create new innovations. One of the innovations created is the emergence of the concept of electronic learning (e-learning). E-learning is useful for students and teachers to get learning materials easily, one of which is by using e-module teaching materials. This study aims to determine the process and produce a product in the form of an e-module of teaching materials assisted by algebrator software on the material of rank numbers and root forms for class X SMK. This type of research is development using ADDIE floating model. The instrument used in this study is a non-test instrument, namely a validation questionnaire, and the data obtained from a validation questionnaire that has been filled out by the validator. The data will be analyzed descriptively quantitatively. Overall, the feasibility of the e-module assisted by algebrator software on the material of numbers and root forms obtained an average of 86.35%, so that the e-module assisted by algebrator software on the material of numbers and roots of class X SMK is interpreted as very valid to use.Â Kata Kunci: E-module, Algebrator Software, Exponents and Roots, Validity